Occurrence of Esophageal Atresia With Tracheoesophageal Fistula in Siblings From Three-Generation Family Affected by Variable Expressivity MYCN Mutation: A Case Report - Klaniewska, Magdalena; Toczewski, Krystian; Rozensztrauch, Anna; Bloch, Michal; Dzielendziak, Agata; Gasperowicz, Piotr; Slezak, Ryszard; Ploski, Rafał; Rydzanicz, Małgorzata; Smigiel, Robert; Patkowski, Dariusz (Frontiers in Pediatrics, 2021)
The MYCN oncogene encodes a transcription factor belonging to the MYC family. It is primarily expressed in normal developing embryos and is thought to be critical in brain and other neural development. Loss-of-function variants resulting in haploinsufficiency of MYCN, which encodes a protein with a basic helix–loop–helix domain causes Feingold syndrome (OMIM 164280, ORPHA 391641). We present an occurrence of esophageal atresia (EA) with tracheoesophageal fistula in siblings from a three-generation family affected by variable expressivity of MYCN mutation p.(Ser90GlnfsTer176) as a diagnostic effect of searching the cause of familial esophageal atresia using NGS-based whole-exome sequencing (WES). All of our affected patients showed microcephaly and toe syndactyly, which were frequently reported in the literature. Just one patient exhibited clinodactyly. None of the patients exhibited brachymesophalangy or hypoplastic thumbs. The latest report noted that patients with EA and Feingold syndrome were also those with the more complex and severe phenotype. However, following a thorough review of the present literature, the same association was not found, which is also confirmed by the case we described. The variable phenotypic expression of the patients we described and the data from the literature guide a careful differential diagnosis of Feingold syndrome even in cases of poorly expressed and non-specific symptoms.